The Effect of Noni Leaves’ Age Variation On the Value of Absorbance and Wavelength In Certain Color Spectrums - Kasyfi Rifqi Mouromadhoni; Heru Kuswanto; Andi Asmar (STKIP Singkawang, 2019)
This research is experimental research. The research aims to analyze the absorbance and wavelength values on the certain color spectrum based on the age of noni leaf sample. Variation in absorption and wavelength occurs in the red spectrum ranges between 650 to 700 nm. Maximum absorption occurs in the middle of noni leaf followed by the tip of noni leaf sample but the yellow leaf sample results poor absorption. Chlorophyll a has main leaf pigment the most which occurs in the light reaction of photosynthesis. The maximum absorption which ranges between 3,5 to 4,0 A occurs in the blue spectrum ranges between 400 to 450 nm. Chlorophyll b absorbs photon energy in sun light. A wavelength ranges between 500 to 600 nm occurs in the green spectrum which has low absorption of three samples ranges 0,5 to 1,5 A. The chlorophyll reflects light of the green spectrum; therefore, it causes low absorption.